PERAN BIDAN DALAM PELAYANAN ANC MELALUI MEDIA ONLINE TERHADAP KEPATU-HAN IBU HAMIL DALAM K1-K4 DALAM MASA PANDEMI COVID-19 DI PUSKESMAS BERU KABUPATEN SIKKA - Regina Ona Adesta; , Maria Susana Ine Nona Ringgi; Emanuela Natalia Nua (Indonesian National Nurses Association (INNA) of Central Java, 2022)
Background: Pregnant women are one of the population vulnerable to a disease. Therefore, pregnant women need to increase vigilance by limiting visits, namely by conducting online consultations or online media. Research Target: This study aims to determine the role of midwives in ANC services through online media on the compliance of pregnant women in K1-K4 during the Covid-19 pandemic. Method: The research design used was a quasi-experimental research design with Posttest only control group design. The sample in this study were all midwives who served in the work area of ​​the Beru Health Center as many as 45 midwives. The sampling method used in this research is non-probability sampling, with the technique used is total sampling. Results of Research: The analysis used the chi square test of 2 samples (p = 0.002), meaning that there was a significant difference in the compliance of pregnant women between the group of midwives who used online media and those who did not use online media. Suggestion: This research is expected to help midwives to be more active in using online media to control the health of pregnant women, thereby reducing direct contact for longer and reducing the transmission of the covid-19 virus.